Southern Cone Memory Discourse and Cuba’s Generación de los Hijos in Camila Guzmán Urzúa’s El telón de azúcar (2006) - Renker, Tess (Revista Canadiense de Estudios Hispánicos, 2022)
The present article analyzes the documentary Telón de azúcar (2006) by Cuban filmmaker Camila Guzmán Urzúa (1971) and the cinematic dialogue she sustains with the work of her father, Chilean documentarian Patricio Guzmán. Although the documentary primarily deals with Cuba and the impact of the Special Period on the filmmaker’s generation, the article proposes that Guzmán Urzúa, upon borrowing audiovisual discourses and techniques from her father’s post-dictatorship cinematography, develops a searing critique of the revolutionary dream of her parents’ generation, even as she maintains her faith in socialist futures.